Liouville Property for a Class of Quasi-Harmonic Sphere (Analysis in Theory and Applications, 2018)
In this paper we obtain a Liouville type result for a class of quasi-harmonic spheres with rotational symmetry.
Keywords: Liouville property; quasi-harmonic sphere; rotational symmetry.